Um guardião do udenismo : a trajetória política de José Fragelli (1934-1971) - Araújo, Vinicius de Carvalho (2022)
The main purpose of this thesis is to identify how the axis of udenism, regionalism and the defense of the political and economic interests of the ranchers in the South of Mato Grosso guided the political trajectory of José Fragelli between the years of 1945 to 1971. The specific objectives include the definition of udenism and regionalism and description of the ranchers elite in the South of Mato Grosso. Here are their political and economic interests, together with the demonstration of the social and political links of José Fragelli with this group. At last, the thesis intents to identify how José Fragelli organized his political militancy in the positions of federal and state deputy and partisan manager according the proposed axis. The adopted methodology covers the concepts developed by the New Political History and the contemporary conception of biography. In the case of political history the thesis is aligned with the movement that rehabilitated the power as na object of historiographic study and placed it in the first plan. The Pierre Rosanvallon´s proposal is central, because he advanced in this comprehension of pluridisciplinarity through the notion of conceptual history of the political. Another strong reference was developed by the Núcleo de Estudos e Pesquisas do Rio de Janeiro do Centro de Pesquisa e Documentação de História Contemporânea da Fundação Getúlio Vargas (CPDOC/FGV), centered in features like the signaling of the worries of the internal dynamics of the local groups´s political struggles; identification of the bonds with the central power, always in a two way street; emphasis in the political and institutional engineering operations; subscription of the works among the studies of political elites; the concentration in the political trajectories; and the incorporation of the symbolic dimension, generating a sophisticated analysis of the politics. The biography was selected for its alignment with the historiographic debate around the relations between indidivual and society, according with the new biographic narrative. Based in the positions occupied by José Fragelli and his strategies, it was possible to understand the broader features of the political field, as well as its structural and conjuncture conditionings. Moreover, the biography, in the form proposed for this thesis, could provide the integration among history, journalism, literature, political science and sociology. The concepts developed by Giovani Levi, François Dosse and Pierre Bourdieu also took part in the theoretical framework. The selected documentation includes José Fragelli or close people’s personal mailing approaching political e private themes; minutes and other recordings of Legislative Assembly of the State of Mato Grosso and the Deputy Chamber ; testimonials of the biographed himself, members of his Family and the political elite; bibliography; monographies, thesis and dissertations, jornalistic sources, audiovisual, cientific articles; Mato Grosso government´s documents and of the faculty of law in the São Paulo University (Usp). The preliminary results point to a strong alignment of the José Fragelli´s political trajectory with the proposed axis to the analysis. It became very clear in the political positioning assumed by him and the taken decisions in the diferentes conjunctures covered by the thesis.